Peningkatan keterampilan kelompok IRT Nelayan melalui teknologi diversifikasi pangan berbasis olahan Ikan Lomek di Desa Buruk Bakul Kabupaten Bengkalis - Nursyirwani Nursyirwani; Ummi Mardiah Batubara; Tjipto Leksono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Buruk Bakul Village is a coastal area that is one of the suppliers of fishery products in Riau Province. This community service (CS) aims to improve the skills of the woman fishermen in Buruk Bakul Village to process the Lomek fish into feature products. The stages of the Programs were a) approach and socialization, b) training and skill improvement, and c) group assistance, monitoring, and evaluation. The CS program involved 20 members of the woman fishermen and UNRI 2022 integrated KKN students. The result of the program showed increased knowledge after training on diversification techniques by up to 95%. The results of monitored and evaluation showed that 93% of participants stated that the program was beneficial. The analysis of the sustainability of the programs reported that there were two types of training desired by the woman fishermen in the Buruk Bakul Village, sequentially, 1) processing food from other fishery materials and 2) package product training.